2020
DOI: 10.1111/inr.12572
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based policy: nursing now and the importance of research synthesis

Abstract: Aim This study explores how scholarship relating to meta‐analytical studies and systematic and integrative reviews can inform nursing’s contribution to universal health coverage. Introduction As nursing globally embraces the 200th anniversary of the birth of Florence Nightingale, the Nursing Now social movement has called for the profession to improve universal health coverage through increasing nursing’s policy voice. Methods In determining how the Nursing Now social movement could pursue the aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…In this sense, the category “Labor and health: nursing implications for the healthy development of labor and workers” shows that nurses can promote dignified and fair labor, in order to favor economic growth. Hence, the training of nursing PhDs is also committed with fighting unbalances and defending systems and actions that promote opportunities for inclusive economic growth for all [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the category “Labor and health: nursing implications for the healthy development of labor and workers” shows that nurses can promote dignified and fair labor, in order to favor economic growth. Hence, the training of nursing PhDs is also committed with fighting unbalances and defending systems and actions that promote opportunities for inclusive economic growth for all [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at the individual organizational and sub‐organizational levels, the impact of such activity can have a near‐immediate impact on the role that the profession plays in the delivery of person‐centred care (Ghebrehiwet, ). More recently, Benton et al () demonstrated that a wealth of material is available in the form of meta‐analytical, systematic and integrative reviews that can be used to produce policy briefs on topics supportive of the attainment of UHC and other SDGs as well as a diverse range of issues relevant to addressing today’s health needs. As noted in the WHO () monitoring report, while some success has been made towards attaining UHC, progress is still too slow.…”
Section: Discussionmentioning
confidence: 99%
“…Crisp () highlighted an enormous, worldwide increase in non‐communicable diseases (NCDs) such as diabetes. Benton et al () confirmed the availability of a wealth of evidence to address this health challenge, and the WHO () has provided up‐to‐date information on its magnitude at both aggregate and country levels. Furthermore, with diabetes as the exemplar, it is possible to demonstrate how nursing solutions can be used to simultaneously resolve the four other dimensions that Crisp () suggests should be addressed as part of the Nursing Now campaign.…”
Section: An Exemplar Of a Nursing Contribution To Uhcmentioning
confidence: 97%
See 1 more Smart Citation
“…A gap exists between what is known from research and theory and what is actually done in clinical practice (Benton, Watkins, Beasley, Ferguson, & Holloway, 2020; Mackey & Bassendowski, 2017). A definitively greater focus on research utilization in clinical practice, constituting the development and usage of empirical research knowledge in practice (Estabrooks, 1999), has been applied in the past 50 years to move closer to evidence‐based practice (Mackey & Bassendowski, 2017).…”
Section: Introductionmentioning
confidence: 99%